2017
DOI: 10.1002/cssc.201700760
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Reactive Oxygen Species in Anion Exchange Membrane Fuel Cells using In Situ Fluorescence Spectroscopy

Abstract: The objectives of this study were: 1) to confirm superoxide anion radical (O ) formation, and 2) to monitor in real time the rate of O generation in an operating anion exchange membrane (AEM) fuel cell using in situ fluorescence spectroscopy. 1,3-Diphenlisobenzofuran (DPBF) was used as the fluorescent molecular probe owing to its selectivity and sensitivity toward O in alkaline media. The activation energy for the in situ generation of O during AEM fuel cell operation was estimated to be 18.3 kJ mol . The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 40 publications
(94 reference statements)
1
41
0
Order By: Relevance
“…A, Zn‐TCPP nMOF generated abundant 1 O 2 under 5 min irradiation of a 650 nm laser (0.6 W/cm 2 ) and also exhibited concentration‐depended production of 1 O 2 (Supporting Information Fig. 2), which caused continuously decreased fluorescence intensity of DPBF at 480 nm . As expected, negligible intensity variation has been detected in the control group.…”
Section: Resultssupporting
confidence: 54%
“…A, Zn‐TCPP nMOF generated abundant 1 O 2 under 5 min irradiation of a 650 nm laser (0.6 W/cm 2 ) and also exhibited concentration‐depended production of 1 O 2 (Supporting Information Fig. 2), which caused continuously decreased fluorescence intensity of DPBF at 480 nm . As expected, negligible intensity variation has been detected in the control group.…”
Section: Resultssupporting
confidence: 54%
“…Such loss of VBTMA-OH was associated to the formation and subsequent attack of superoxide radical (SOR) due to the high concentrations of oxygen during normal fuel cell operating conditions. [19,20] Chang et al [21,22] also reported similar oxidative degradation mechanism observed with polybenzimidazole-based membranes for fuel cells. Consequently, the use of radical inhibitors such as p-ethyl phenol [23] and radical scavengers [24] has been proposed to minimise or control oxidative degradation of polymerbased AEMs.…”
Section: Introductionmentioning
confidence: 65%
“…The polyaromatic nature of the SPEEK backbone will make it resistant to oxidation by ROS. The ROS expected in the catholyte will be superoxide as this species is favored under alkaline conditions [ 54 , 55 ]. Strong oxidizing agents like hydroxyl and hydroperoxyl radicals, formed from the decomposition of hydrogen peroxide (parasitic product from oxygen reduction), are favored under acidic conditions [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%